2010
DOI: 10.4161/auto.6.1.10814
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and adipogenesis: Implications in obesity and type II diabetes

Abstract: specific deletion of autophagy-related gene 7 (atg7) in mice reveals a role in adipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…In this regard, inhibiting mitochondrial fission decreases glucose-stimulated insulin secretion in b-cells by accumulating dysfunctional mitochondria resulting from dysregulated autophagy (171). It has been reported that autophagy is associated with diabetes (62,68,110,111,113). It is evident that mitochondrial fission and fusion play an important role in metabolism-secretion coupling of pancreatic b-cells by regulating bioenergetics and homeostasis of mitochondria.…”
Section: Mitochondrial Dynamics In Pancreatic B-cells and Insulin Secmentioning
confidence: 99%
“…In this regard, inhibiting mitochondrial fission decreases glucose-stimulated insulin secretion in b-cells by accumulating dysfunctional mitochondria resulting from dysregulated autophagy (171). It has been reported that autophagy is associated with diabetes (62,68,110,111,113). It is evident that mitochondrial fission and fusion play an important role in metabolism-secretion coupling of pancreatic b-cells by regulating bioenergetics and homeostasis of mitochondria.…”
Section: Mitochondrial Dynamics In Pancreatic B-cells and Insulin Secmentioning
confidence: 99%
“…Adipocyte-specific Atg7-knockout mice exhibited adipocytes with features more characteristic of brown fat than of white AT, being heterogeneous, smaller, containing multiple small lipid droplets and a significant amount of cytoplasm, in contrast to the typical homogenous unilocular cells of wild-type mice. Cells also exhibited a markedly increased number of mitochondria [12,13,18]. At the whole body level white fat depots (gonadal, scapular) were about 20% smaller, with whole body weight being consistently lower.…”
Section: Autophagy and Adipose Tissue Developmentmentioning
confidence: 99%
“…1,2 Recent studies have shown that autophagy is upregulated in adipocytes from diabetic mice or obese patients. [3][4][5][6][7][8] Adipose-specific deletion of a key autophagy gene, such as atg5 or atg7, led to lean mice and improved insulin sensitivity and glucose homeostasis in the whole body of mice. 6,7,9 One of the key features with the mouse models was a reduction in the white adipose tissue (WAT) mass, and an increase in the brown adipose tissue (BAT) mass.…”
Section: Introductionmentioning
confidence: 99%